Near-peer mentorship as a welcome ritual: Exploring the what and how of McGill’s “Buddy program” - Moussa, Sarah; Islam, Nehal; Datta, Aurgho; Hassan, Abdullatif; Hassan, Adam (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2025)
Implication StatementSince 2015, the “Buddy Program,” a near-peer mentoring program operated by the McGill Student Society, has successfully welcomed 1,152 first-year medical students into medical school with the help of 848 dedicated second-year medical student mentors. This innovative, low-cost, time-efficient, automated and scalable model offers a reproducible framework and toolkit for similar institutions that wish to realize the benefits of near-peer mentoring. With unique features such as matching based on personal interests and continual improvements, such as the Meet-&-Greet event and associated orientation booklets, the program is a pioneering example of student-run near-peer mentorship.